2020
DOI: 10.3233/hsm-190796
|View full text |Cite
|
Sign up to set email alerts
|

Human capital development: A construct for underprivileged students

Abstract: Preparing underprivileged students to become human capital is a challenge. Issues relating to motivation and behavior are often cited as a roadblock in for quality of their learning and development. The primary goal of this study is to develop a construct as a foundation for future design and improvement to ensure successful human capital development for underprivileged students. The proposed construct is derived from the case study with Bangkok Metropolitan Administration since 2016. Observation and interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The school-to-work transition is a critical juncture in shaping the career futures of at-risk youth (Lifshitz, 2017). Consequently, as Kongtong et al (2020) indicated, preparing disadvantaged students to become human capital is challenging. Motivational and behavioural issues are often cited as a barrier to the quality of their learning and development.…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%
“…The school-to-work transition is a critical juncture in shaping the career futures of at-risk youth (Lifshitz, 2017). Consequently, as Kongtong et al (2020) indicated, preparing disadvantaged students to become human capital is challenging. Motivational and behavioural issues are often cited as a barrier to the quality of their learning and development.…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%
“…The school-to-work transition is a critical juncture in shaping the career futures of at-risk youth (Lifshitz, 2017). Consequently, as Kongtong et al (2020) indicated, preparing disadvantaged students to become human capital is challenging. Motivational and behavioural issues are often cited as a barrier to the quality of their learning and development.…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%